Iterative Joint Detection-Decoding Algorithms Using Euclidean Distance-Based Feedback - Ullah, Waheed; Jayakody, Dushantha Nalin K.; Li, Jun; Chursin, Yuri (International Conference on Information and Automation for Sustainability, 2021)
In this article, two algorithms for improving the bit error rate performance of the non-binary LDPC codes over higher order modulation are proposed. The first algorithm is the predictive syndrome based symbol flipping decoding algorithm. The flipping function of this algorithm utilizes the channel reliability to identify the least reliable symbol position. In Algorithm 1, if the predicted symbol value satisfies the check sum, then the candidate symbol value is declared as correct otherwise that value is adjusted and sent back to the QAM detector. Algorithm 2 in this paper is an improvement to iterative joint detection-decoding algorithm by using the method of iterative hard decision based majority logic to select the new candidate symbol value. The feedback value to the QAM detector is adjusted by using Euclidean distance between the current symbol and the newly selected symbol value. Numerical results and complexity analysis show that the proposed schemes have better bit error rate versus complexity trade-off in comparison to some of the existing algorithms.